2011
DOI: 10.1371/journal.pone.0021841
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Health-Related Quality of Life in Elders with Frailty: A Cross-Sectional Study of Community-Dwelling Elders in Taiwan

Abstract: PurposeExploring the domains and degrees of health-related quality of life (HRQOL) that are affected by the frailty of elders will help clinicians understand the impact of frailty. This association has not been investigated in community-dwelling elders. Therefore, we examined the domains and degree of HRQOL of elders with frailty in the community in Taiwan.MethodsA total of 933 subjects aged 65 years and over were recruited in 2009 from a metropolitan city in Taiwan. Using an adoption of the Fried criteria, fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
106
2
6

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 24 publications
11
106
2
6
Order By: Relevance
“…We identified seven studies which reported pain outcomes in older people with frailty (table 1). One study was conducted in Canada 11,17 , one in Australia 18,19 , one in Finland 20 , two in Taiwan 13,21 , and two in Brazil 22,23 . The mean age of participants ranged from 71 years to 82 years (see table 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified seven studies which reported pain outcomes in older people with frailty (table 1). One study was conducted in Canada 11,17 , one in Australia 18,19 , one in Finland 20 , two in Taiwan 13,21 , and two in Brazil 22,23 . The mean age of participants ranged from 71 years to 82 years (see table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The proportion of frail participants ranged in the studies from 9% to 32%. Four studies used questions from the SF-12 or SF-36 to assess pain 11,13,19,23 . Chang et al 21 reported the presence of pain history but did not report the specific measure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…reducing the quality of life level. (9) In addition, as a result of the institutionalization, these effects can be enhanced.…”
Section: Resultsmentioning
confidence: 99%